Bioaccumulation and emission of organophosphate esters in plants affecting the atmosphere's phosphorus cycle. (1st February 2023) - Long, Shengxing; Hamilton, Paul B.; Fu, Bo; Xu, Jing; Han, Luchao; Suo, Xinhao; Lai, Yuqin; Shen, Guofeng; Xu, Fuliu; Li, Bengang
Abstract: The imbalance of atmospheric, terrestrial and aquatic phosphorus budgets remains a research conundrum and global concern. In this work, the uptake, distribution, bioaccumulation and emission of organophosphate esters (OPEs) by clove trees ( Syzygium aromaticum ), lemon trees ( Citrus limon ) and cape jasmine trees ( Gardenia jasminoides var. fortuniana ) was investigated as conduits for phosphorus transfer or sinks and sources. The objective was to assess the role OPEs in soils play as atmospheric phosphorus sources through plant bioaccumulation and emission. Results demonstrated OPEs in experimental soil plots ranging from 0.01 to 81.0 ng g −1 dry weight, were absorbed and transported through plants to the atmosphere. The total emission of OPEs varied greatly from 0.2 to 588.9 pg g −1 L −1 h −1, with a mean of 47.6 pg g −1 L −1 h −1 . There was a negative linear relationship between the concentrations of total phosphorus and four OPEs, tri-iso-butyl phosphate, tri-n-butyl phosphate, tris (2-chloroisopropyl) phosphate and tripentyl phosphate. Trimethyl phosphate levels were positively correlated with total nitrogen, and the concentrations of tri-iso-butyl phosphate, tri-n-butyl phosphate, tris (2-chloroisopropyl) phosphate and tripentyl phosphate decreased along with available potassium in leaves after 72 h. There was a significantly positive linear relationship between higher emission concentrations of OPEs and the emission factor of OPEs concentration ( F = 4.2, P = 0.002 ), with lower emissions of OPEs and the bioaccumulation of OPEs in leaves ( F = 4.8, P = 0.004 ). OPEs releases to the atmosphere were enriched in aerosols, and participate in atmospheric chemical reactions like photolysis, thereby affecting the phosphorus balance and cycling in the atmosphere. Graphical abstract: Image 1 Highlights: Eight organophosphate esters were released to the atmosphere from soil via plants. Plant transpiration is key to OPEs transfer with more hydrophilic atmosphere release. OPEs from 0.01 to 81.0 ng g-1 dw in soils are transported from plants to the atmosphere. OPEs emissions significantly decrease with increasing Log K ow and Log K oA . Bioaccumulation and emission factors significantly affect emissions concentration.